2014
DOI: 10.5539/ijef.v6n6p127
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Banking Efficiency in the CEMAC Zone

Abstract: The objective of this study is to analyze the effect of competition on the cost and profit efficiency of banks in the Economic and Monetary Community of Central Africa (CEMAC), over the period [2003][2004][2005][2006][2007][2008][2009][2010]. The analysis is done in two stages. First, the stochastic frontier approach (SFA) permits us to estimate the efficiency scores and the competition levels measured by the adjusted Lerner index. Second, the competition measures thus obtained, and a set of control variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The efficiency, stability of a banking system and access to finance relate to the level of competitiveness of that banking sector (Love and Per´ıa, 2014;Mudd, 2013;Ningaye et al, 2014;Fu et al, 2014;Schaeck and Cih´ak, 2014). Hence the need for a competitive banking system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency, stability of a banking system and access to finance relate to the level of competitiveness of that banking sector (Love and Per´ıa, 2014;Mudd, 2013;Ningaye et al, 2014;Fu et al, 2014;Schaeck and Cih´ak, 2014). Hence the need for a competitive banking system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An extensive body of theoretical and empirical studies has reported the significant role of bank competition in ensuring access to finance (Clarke et al, 2006;Lin et al, 2010;Love and Per´ıa, 2014;Mudd, 2013;Rice and Strahan, 2010;Tan, 2013), efficiency (Mlambo and Ncube, 2011;Ningaye et al, 2014;Pasiouras et al, 2009;PruteanuPodpiera et al, 2008) and stability Fu et al, 2014;Schaeck and Cih´ak, 2014;Ariss, 2010) in any economy. According to Casu et al (2015), competition is good for many reasons; it is an essential force in any economy, it encourages firms to be more efficient and provide better allocation of resources.…”
Section: Introductionmentioning
confidence: 99%